Application of the photogrammetric and the geographic information systems in the urban environment: A case of study - Grilo, R. C. [UNESP]; Foresti, C. [UNESP]; Viadana, M. I.C.F. [UNESP] (My University, 2002)
The urban growth and the environmental relationship are several times joint as to the of the urban soil occupation as to the urban area development. The transformation of the several kinds of soil use and the human being activities related to them happen in all sections of the urban space. Therefore the development of the cities is not always followed by the substructure wanted which is going to roduce during a time environmental problems. The flood occurence is one of the environmental problems which has caused many damages to the inhabiting people from the cities. These problems are due to most of the time to the use and occupation of the soil without anandequated planning, besides the lack of state government management of pluvial water. In the city of Itajubá – MG, the flood has been drastic lately and because of it this study had been done with the objective of analysing the structure and the occupation of the soil integrated to the physical features of this landscape. At this rate, contributing to a more efficient planning, based on the environmental management which provides the citizen rights related to their worth life conditions.
Keywords: Flood; GIS; Photogrammetry; Urbanization; Use of Soil